Cyclin D-CDK4 relieves cooperative repression of proliferation and cell cycle gene expression by DREAM and RB. - Schade, Amy E. (Oncogene, 2019)
The Retinoblastoma protein (RB) restricts cell cycle gene expression and entry into the cell cycle. The RB-related protein p130 forms the DREAM (DP, RB-like, E2F and MuvB) complex and contributes to repression of cell cycle dependent genes during quiescence. Although both RB and DREAM bind and repress an overlapping set of E2F dependent gene promoters, it remains unclear if they cooperate to restrict cell cycle entry. To test the specific contributions of RB and DREAM, we generated RB and p130 knockout cells in primary human fibroblasts. Knockout of both p130 and RB yielded higher levels of cell cycle gene expression in G0 and G1 cells compared to cells with knockout of RB alone, indicating a role for DREAM and RB in repression of cell cycle genes. We observed that RB played a dominant role in E2F dependent gene repression during mid to late G1 while DREAM activity was more prominant during G0 and early G1. Cyclin D - Cyclin Dependent Kinase 4 (CDK4) dependent phosphorylation of p130 occurred during early G1 and led to the release of p130 and MuvB from E2F4 and decreased p130 and MuvB binding to cell cycle promoters. Specific inhibition of CDK4 activity by palbociclib blocked DREAM complex disassembly during cell cycle entry. In addition, sensitivity to CDK4 inhibition was dependent on RB and an intact DREAM complex in both normal cells as well as in palbociclib-sensitive cancer cell lines. Although RB knockout cells were partially resistant to CDK4 inhibition, RB and p130 double knockout cells were significantly more resistant to palbociclib treatment. These results indicate that DREAM cooperates with RB in repressing E2F dependent gene expression and cell cycle entry and supports a role for DREAM as a therapeutic target in cancer.